Crisis and conflict maps in the Web 2.0: A critical look at the new crisis and conflict maps - Michel, Boris; Bittner, Christian; Glasze, Georg; Turk, Catherine (Geographische Rundschau, 2011)

Das Dekonstruieren der web2.0 Karte. Vorschläge zur Analyse dynamischer und interaktiver Karten multipler und diffuser Autorenschaften - Bittner, Christian; Michel, Boris (Geo@web, 2013)
Keywords: Geoweb; Kritische Kartographie; Web 2.0-Kartographie

Der Kartenlehrer – Jean-Christophe Victor und die didaktische TV-Kartographie „Mit offenen Karten“ - Baumann, Christoph; Bittner, Christian (Kartographische Nachrichten, 2017)

Diversity in volunteered geographic information - Comparing OpenStreetMap and Wikimapia in Jerusalem - Bittner, Christian (Geo Journal, 2016)
While the term “volunteered geographic information” (VGI) has become a buzzword in debates on the geoweb, online cartography and digital geoinformation, the scope and reach of VGI remains underexplored. Drawing on literature on social implications of VGI, this article, firstly, explores differences between VGI initiatives at the example of a comparative case study on social biases within data of OSM and Wikimapia in the fragmented social setting of Jerusalem, Israel. The results of this analysis turn out to be highly contradictive between both projects, which challenges widely accepted assumptions on the imprint of social inequalities and digital divides on VGI. This observation guides, secondly, a discussion of diversity within the category of VGI. Arguing that mapping communities, data formats and knowledge types behind VGI are extremely dissimilar, the paper proceeds by questioning the consistency and utility of VGI as a category. Seeking for a more comprehensive typology of VGI, Edney’s notion of cartographic modes will be presented as an approach towards a more contextualized understanding of VGI projects by embracing their underlying cultural, social and technical relations. Consequently, the paper suggests empirical research on the cartographic modes of a broad series of VGI projects through qualitative and quantitative methods alike.
Keywords: Volunteered geographic information (VGI); · Wikimapia; OpenStreetMap; Geoweb; Cartographic modes

E-Partizipation als neuer Impuls in stadtplanerischen Prozessen? Von den Visionen der Stadtplanenden zu den Utopien der BürgerInnen. - Franz, Katrin; Haidl, Isabela; Hartmann, Kerstin; Lehnhoff, Felix; Riedmann, Sofrony; Bittner, Christian; Orlowski, Benedikt Marko (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2014)
Keywords: E-Partizipation; E-Government; Stadtplanung

Excluding Effects of Cartographic Epistemologies - Thinking About Mapping Paradigms in OpenStreetMap and Wikimapia - Bittner, Christian; Glasze, Georg (Kartographische Nachrichten, 2018)
Although the emergence of collaborative online mapping platforms has radically lowered access barriers to cartographic practices, many studies have shown how participation in online mapping is biased socially towards more privileged groups and geographically towards higher income regions. Yet, exclusion-mechanisms beyond those socio-economic divides have hardly been considered so far. Adding one such possible cause of social exclusion that is not directly linked to socio-economic factors, this paper makes an argument for the consideration of cartographic epistemologies. We illustrate the exclusion-mechanisms of cartographic epistemologies through two exemplary case studies, focusing on the ground-truth agenda of OSM and on Wikimapia’s endeavor to describe the world.
Keywords: Critical Cartography; Epistemology; OpenStreetMap; VGI; Wikimapia

Krisen- und Konflikt-Karten im Web 2.0. Ein kritischer Blick auf die neuen Krisen-und Konfliktkarten - Bittner, Christian; Glasze, Georg; Michel, Boris; Turk, Catherine (Geographische Rundschau, 2011)
UnivIS-Import:2015-04-14:Pub.2011.nat.dgeo.IG.zentr.krisen

(untitled) - Bittner, Christian; Michel, Boris (Handbuch kritische Stadtgeographie)
Keywords: Kartographie; Kritische Kartographie; Stadt

Land use changes in the rural-urban fringe: An Israeli case study - Bittner, Christian; Sofer, Michael (Land Use Policy, 2013)
The paper analyses the changing pattern of land uses in rural settlements located in the rural-urban fringe and makes a link between the results to socio-economic developments and to changes in the rural policy at the national level. Using historical sequences of land use maps and using geostatistical analysis, we observe changing land use patterns in three Moshav type settlements - the most common type of rural settlement in Israel - in three different rural-urban fringes belts along the coastal area. We identify basic trends of specialisation and intensification of agricultural land use as well as expansion of built up structures for residential and commercial purposes. These trends which are rather similar for all three cases, we argue, reflect economic and social changes in rural settlements in general and in the rural-urban fringe in particular. The evolving patterns in the three Moshavim in the Israeli rural-urban fringe (RUF) can be understood as adjustment measures at the household level to development and changing policies at the macro level, particularly towards the rural sector. There are two major domains of change. First, a transition from dependence on farming to a more diversified economic base suggesting newly shaped interrelationships with the urban space. Second, a new residential development program which has rejuvenated failing and ageing rural settlements. The outcome is a major process of restructuring which affects the economic, social and environmental spheres, and necessitates sensitivity on the part of institutional decision makers towards the complex and diverse realities of relevant actors on the ground, through which all current and future land use policies are mediated. Moreover, being exposed to uncontrolled and often chaotic adjustment measures over the last three decades, it might be necessary to regulate and preserve some of the Moshav's distinct features so it does not to fade into an 'ordinary suburb'. © 2012 Elsevier Ltd.
UnivIS-Import:2015-04-20:Pub.2013.nat.dgeo.IG.zentr.landus
Keywords: Israel; Land use; Moshav; Rural-urban fringe

OpenStreetMap in Israel and Palestine – ‘Game changer’ or reproducer of contested cartographies? - Bittner, Christian (Political Geography, 2017)
In Israel and Palestine, map-making practices were always entangled with contradictive spatial identities and imbalanced power resources. Although an Israeli narrative has largely dominated the ‘cartographic battlefield’, the latest chapter of this story has not been written yet: collaborative forms of web 2.0 cartographies have restructured power relations in mapping practices and challenged traditional monopolies on map and spatial data production. Thus, we can expect web 2.0 cartographies to be a ‘game changer’ for cartography in Palestine and Israel. In this paper, I review this assumption with the popular example of OpenStreetMap (OSM). Following a mixed methods approach, I comparatively analyze the genesis of OSM in Israel and Palestine. Although nationalist motives do not play a significant role on either side, it turns out that the project is dominated by Israeli and international mappers, whereas Palestinians have hardly contributed to OSM. As a result, social fragmentations and imbalances between Israel and Palestine are largely reproduced through OSM data. Discussing the low involvement of Palestinians, I argue that OSM's ground truth paradigm might be a watershed for participation. Presumably, the project's data are less meaningful in some local contexts than in others. Moreover, the seemingly apolitical approach to map only ‘facts on the ground’ reaffirms present spatio-social order and thus the power relations behind it. Within a Palestinian narrative, however, many aspects of the factual material space might appear not as neutral physical objects but as results of suppression, in which case, any ‘accurate’ spatial representation, such as OSM, becomes objectionable.
Keywords: OpenStreetMap; Israel; Palestine; Critical cartography; Web 2.0 cartographies; Volunteered geographic information

Partizipatives Kartieren als Praxis einer kritischen Kartographie - Bittner, Christian; Michel, Boris (Sozialraum erforschen: Qualitative Methoden in der Geographie, 2018)

Qualitative Geographische Informationssysteme - Bittner, Christian; Michel, Boris (Sozialraum erforschen: Qualitative Methoden in der Geographie, 2018)

Reproduktion sozialräumlicher Differenzierungen in OpenStreetMap: das Beispiel Jerusalems - Bittner, Christian (Kartographische Nachrichten, 2014)
Keywords: OpenStreetMap; Volunteered Geographic Information; Geoweb; Kartographie; Jerusalem

Tracing contingencies: Analyzing the political in assemblages of web 2.0 cartographies - Bittner, Christian; Glasze, Georg; Turk, Catherine (Geo Journal, 2013)
Our paper presents a theoretical approach to critical research on web 2.0 cartographies. Within the geoweb, dynamic and collaborative web based maps have become a popular medium for collating and communicating geographic information. Web 2.0 cartographies are often promoted as facilitating public participation and democratizing geographic knowledge. Such claims demand a closer look at the processes through which people do engage in these cartographic projects and the multiple actors, institutions, norms and technologies at work. In the context of 'theorizing the geoweb', here we propose conceptual tools for analyzing these myriad interactions within web 2.0 cartographies. We understand web 2.0 cartographies as assemblages of subjects, materialities and practices, or 'actor networks'. Yet explorations of actor-networks describe existing relations and as a consequence tend to overlook what has been excluded or lies outside of such assemblages. In order to overcome this blindness we suggest bringing together actor-network theory with the concepts of hegemonic discourses, contingency and the political from Chantal Mouffe and Ernesto Laclau. These two political theorists stress the idea that specific social realities become fixed, sedimented and perceived as natural while other possible social realities become marginalized. Using the example of the dynamic 'Palestine Crisis Map' (an Ushahidi Crowdmap) we demonstrate a methodology that emphasizes sensitivity towards moments of exclusion and struggle, where the political unfolds. Theorizing the political in this way extends the processual approach within Critical Cartography and offers a conceptual basis for critical research on the social dimensions of web 2.0 cartographies and geoweb practices. © 2013 Springer Science+Business Media Dordrech
Keywords: Actor-network theory; Critical cartography; Geoweb; Theory of discourses and hegemonies; Web 2.0 cartography

Turning the spotlight on the crowd: examining participatory ethics and practices of crisis mapping - Michel, Boris; Turk, Catherine; Bittner, Christian (ACME : An International e-Journal for Critical Geographies, 2016)

Wie gestalte ich eine Karte? - Bittner, Christian (Entgrenzt : studentische Zeitschrift für Geographisches, 2015)